Spatial navigation questionnaires as a supportive diagnostic tool in early Alzheimer's disease - Laczó, Martina; Svatkova, Radka; Lerch, Ondřej; Martinkovic, Lukas; Zuntychova, Terezie; Nedelska, Zuzana; Horakova, Hana; Vyhnalek, Martin; Hort, Jakub; Laczó, Jan (iScience, 2024)
Impaired spatial navigation is early marker of Alzheimer's disease (AD). We examined ability of self- and informant-reported navigation questionnaires to discriminate between clinically and biomarker-defined participants, and associations of questionnaires with navigation performance, regional brain atrophy, AD biomarkers, and biomarker status. 262 participants (cognitively normal, with subjective cognitive decline, amnestic mild cognitive impairment [aMCI], and mild dementia) and their informants completed three navigation questionnaires. Navigation performance, magnetic resonance imaging volume/thickness of AD-related brain regions, and AD biomarkers were measured. Informant-reported questionnaires distinguished between cognitively normal and impaired participants, and amyloid-β positive and negative aMCI. Lower scores were associated with worse navigation performance, greater atrophy in AD-related brain regions, and amyloid-β status. Self-reported questionnaire scores did not distinguish between the groups and were weakly associated with navigation performance. Other associations were not significant. Informant-reported navigation questionnaires may be a screening tool for early AD reflecting atrophy of AD-related brain regions and AD pathology.